Seasonal Variations in Western North Atlantic Remote Marine Aerosol Properties. Issue 24 (27th December 2019) - Quinn, P.K.; Bates, T.S.; Coffman, D.J.; Upchurch, L.; Johnson, J.E.; Moore, R.; Ziemba, L.; Bell, T.G.; Saltzman, E.S.; Graff, J.; Behrenfeld, M.J.
Abstract: The impact of ocean ecosystems on marine boundary layer aerosols and clouds has been the subject of much research but remains uncertain. Five experiments were recently conducted in the western North Atlantic to assess if the seasonally recurring phytoplankton bloom affects aerosol properties. These experiments include the second Western Atlantic Climate Study and four North Atlantic Aerosols and Marine Ecosystem Study cruises. Measurements of unheated and heated number size distributions, cloud condensation nucleus (CCN) concentrations, and aerosol composition were used to identify primary and secondary aerosol components that could be related to the state of the bloom. Only periods of clean marine air, as defined by radon, particle number concentrations, aerosol light absorption coefficient, and back trajectories, were included in the analysis. Nonvolatile material was found to be prevalent in the Aitken mode size range after heating to 230°, likely due to downward mixing from the free troposphere. CCN concentrations at 0.1% supersaturation were best correlated ( r 2 = 0.73) with accumulation mode nss SO4 = . Sea spray aerosol was only correlated with CCN during November when bloom accumulation had not yet occurred and dimethylsulfide concentrations were at a minimum. The fraction of CCN attributable to sea spray aerosol was less than 20% during March, May/June, and September, indicating the limited contribution of sea spray aerosol to the CCN population of the western North Atlantic atmosphere. The strongest link between the plankton bloom and aerosol and cloud properties appears to be due to biogenic non‐sea salt SO4 = . Key Points: Nonvolatile material in the Aitken mode after heating to 230 °C occurs in all seasons likely due to downward mixing from aloft Nonsea salt sulfate links the phytoplankton bloom to cloud condensation nuclei (CCN) during bloom climax Sea spray aerosol only makes up a significant fraction of CCN in November when phytoplankton bloom accumulation has not begun